Mineralogical and geochemical proxies of Miocene sediments of Eastern Azerbaijan: Provenance and oil-bearing - Baloglanov, Elnur; Yolchuyeva, Ulviyya; Akhundov, Ruslan; Samedov, Elmar; Mustafayev, Kamal (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Problem statement. This study explores unconventional hydrocarbon resources in East Azerbaijan, focusing on oil-bearing rocks in the Cheyildere and Gyrgyshlag-Girdagh areas. It examines the spatial and temporal distribution of minerals and chemical compositions in Miocene formations. Terrigenous quartz types identified in the Maikop (Lower Miocene), Chokrak (Lower Miocene), and Diatom (Middle to Upper Miocene) formations provide insights into sedimentological maturity. Geochemical classification and tectonic discriminant diagrams help interpret the protoliths of these sediments. The study also evaluates how mineralogy and moisture affect oil-bearing potential, offering useful data for future exploration and resource management.Purpose. This study aims to explore the genesis and potential of oil-bearing deposits of the Miocene age in East Azerbaijan by characterizing the geological, mineralogical, and geochemical proxies of samples collected from outcrops across various regions.Methods. The mineralogical composition of samples was analyzed using a MiniFlex 600 diffractometer. Chemical composition was determined using S8 TIGER Series 2 and Agilent 7700 Series ICP-MS spectrometers.Results. The geological characteristics of oil-bearing deposits from the Miocene stratigraphic unit were thoroughly analyzed, providing new insights into the distribution patterns of oil-bearing formations and strata within the studied areas. The mineralogical composition was examined in detail, focusing on the spatial and temporal variations in mineral distribution across different formations of Miocene. The chemical composition reveals significant differences between formations in terms of elemental signatures. The study of the chemical proxies enabled the identification of specific terrigenous quartz types. Additionally, the research assessed the influence of mineralogical composition, moisture and oil content on the oil-bearing capacity. The results demonstrated a clear relationship between the mineralogical characteristics and the oil-bearing potential of the rocks.Conclusions. The Chokrak Formation is of particular interest due to its significant oil-bearing potential, with total thicknesses of up to 40 meters in Miocene outcrops studied in the areas of Cheyildere and Gyrgyshlag-Girdagh. Compared to other areas, the Chokrak Formation is dominated by quartz minerals (>70%), while the oil-bearing rocks of this formation contain fewer clay minerals and no carbonate minerals. The Upper Maikop deposits are characterized by calcite, and the Diatom deposits by dolomite.Most oil-bearing rocks of Maikop and Diatom age correlate with greywacke and litharenite, while Chokrak rocks with higher silicon content show a connection with subarkose and sublitharenites. For Diatom oil-bearing rocks, in addition to quartzitic sedimentary sources, some moderate and acidic magmatic rocks can also be considered. Chokrak horizon deposits, rich in quartz, have a more mature mineralogical nature. These deposits, associated with passive continental margins, are typically linked to the interior of cratons or recycled orogenic regions, suggesting long-distance transport.Relatively moist samples containing clay and carbonate minerals exhibit a significantly higher oil accumulation potential than samples with high quartz content. From this perspective, the marly rocks of the Meotis are of particular interest.